2007
DOI: 10.1111/j.1442-2042.2007.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene Taq I polymorphism with recurrent urolithiasis in children

Abstract: Taq I t allele of the VDR gene may be a risk factor for severe urolithiasis and recurrent stone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 18 publications
3
20
0
3
Order By: Relevance
“…Some of these polymorphic forms of VDR are associated with reduced effectiveness of vitamin D, which may lead to higher risk and predisposition to various bone and endocrine diseases, such as osteoporosis, rickets, urolithiasis, and diabetes mellitus type 1. [4][5][6][7][8][9] The pathogenesis of idiopathic nephrotic syndrome (INS) remains inconclusive and controversial and is considered to be mediated by the immune system and the imbalance between T-helper cell subtype 1 (Th1) and Th2 cytokines, which are in turn regulated by 1,25-dihydroxy D3, which is the active form of vitamin D. Vitamin D exerts its effects through its receptor (VDR), which plays a role in the transcriptional inhibition of cytokine genes, subsequently affecting cytokine release. 10 Ethnic and genetic differences in the frequencies of the VDR polymorphic genotypes have been previously reported in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these polymorphic forms of VDR are associated with reduced effectiveness of vitamin D, which may lead to higher risk and predisposition to various bone and endocrine diseases, such as osteoporosis, rickets, urolithiasis, and diabetes mellitus type 1. [4][5][6][7][8][9] The pathogenesis of idiopathic nephrotic syndrome (INS) remains inconclusive and controversial and is considered to be mediated by the immune system and the imbalance between T-helper cell subtype 1 (Th1) and Th2 cytokines, which are in turn regulated by 1,25-dihydroxy D3, which is the active form of vitamin D. Vitamin D exerts its effects through its receptor (VDR), which plays a role in the transcriptional inhibition of cytokine genes, subsequently affecting cytokine release. 10 Ethnic and genetic differences in the frequencies of the VDR polymorphic genotypes have been previously reported in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies about common allelic variations in VDR in disorders of calcium metabolism, using Bsm I, Apa I, Taq I and Fok I restriction enzymes have been performed, but the results were controversial [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. While some studies disclosed an association between VDR polymorphism and bone mineral density (BMD) [12,13,14,15], others did not [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…We thought that having a bb allele could be an independent risk factor for stone formation in normocalciuric infants, but in other studies from Turkey, Gunes et al 21 and Ö zkaya et al 24 found no significant association between BsmI VDR polymorphism and stone formation, nor did Relan et al 9 In this study, TaqI distribution differed significantly between the study and control groups, but ApaI did not. In contrast, Ozkaya et al 24 and Seyhan et al 25 found that the frequency of the ApaI AA genotype was significantly higher in the children with calcium nephrolithiasis than Gunes found no significant association of TaqI and ApaI with urolithiasis. 21 Nishijima et al 26 reported results somewhat similar to ours, finding that TaqI TT and tt genotypes are significantly higher in stone formers, and that the ApaI genotype is similar between the controls and stone formers.…”
Section: Discussionmentioning
confidence: 90%